120 W lithium triborate laser for photoselective vaporization of the prostate: comparison with 80 W potassium-titanyl-phosphate laser in an ex-vivo model - Heinrich, Elmar; Wendt-Nordahl, Gunnar; Honeck, Patrick; Alken, Peter; Knoll, Thomas; Michel, Maurice Stephan; Häcker, Axel (Journal of endourology, 2010)
Purpose: To evaluate the ablative and hemostatic properties of the recently introduced 120 W lithium triborate (LBO) 532 nm laser and compare the results against the conventional 80 W potassium-titanyl-phosphate (KTP) laser. - - Materials and Methods: The ex-vivo model of the isolated blood-perfused porcine kidney was used to determine the ablation capacity, hemostatic properties, and coagulation depth of the GreenLight HPS laser system (American Medical System, Minnetonka, MN) that used an output power of 120 W. The results were compared with the KTP laser that used output power levels of 30 W, 50 W, and 80 W. Unperfused kidneys were weighed before and after 10 minutes of laser ablation in an area of 3 × 3 cm; the weight difference marked the amount of removed tissue. Bleeding was determined by the weight difference of a swab before and after it was placed on the bleeding surface for 60 seconds after ablating a surface area of 9 cm2 on blood-perfused kidneys. - - Results: With a tissue removal of 7.01 ± 1.83 g after 10 minutes of laser ablation at 120 W, the LBO laser offered a significantly higher ablation capacity compared with 3.99 ± 0.48 g reached with the conventional KTP laser at 80 W in the same time interval (P < 0.05). The bleeding rate was also significantly increased using the LBO at 120 W compared with the conventional device at 80 W (0.65 ± 0.26 g/min vs 0.21 ± 0.07 g/min; P < 0.05). The corresponding depths of the coagulation zones were 835 ± 73 μm and 667 ± 64 μm (P < 0.05), respectively. - - Conclusion: The 120 W LBO laser offers a significantly higher tissue ablation capacity compared with the conventional 80 W KTP laser. Because the increased efficacy of the device is accompanied by a higher bleeding rate and a slightly deeper coagulation zone, the user has to select the appropriate output power levels carefully for a safe and efficient treatment. Nevertheless, the bleeding rate compared with previous studies of transurethral resection of the prostate is significantly reduced.